1988
DOI: 10.1117/12.945247
|View full text |Cite
|
Sign up to set email alerts
|

Practical Perspectives On The In-Vitro And In-Vivo Evaluation Of A Fiber Optic Blood Gas Sensor

Abstract: A new optical fluorescence -based microsensor has been developed to continuously monitor intra-arterial blood gases (pH, pCO2, p02) with a probe sufficiently small to share the lumen of a 20 gauge arterial catheter without compromising pressure fidelity or ease of blood withdrawal. The evaluation of performance has proceeded through a combination of in-vitro, animal and clinical studies.Each has had its own unique problems. This series of studies has re-emphasized the fact that acceptable clinical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A microprocessor processes all the detected signals, giving the read-out of the three measurands on a monitor. The described probe (OD = 0.6 mm) has been tested in vivo on animals [36,37], exhibiting satisfactory correlation with data obtained ex vivo from electrochemical blood gas analysers.…”
Section: Blood Phmentioning
confidence: 63%
“…A microprocessor processes all the detected signals, giving the read-out of the three measurands on a monitor. The described probe (OD = 0.6 mm) has been tested in vivo on animals [36,37], exhibiting satisfactory correlation with data obtained ex vivo from electrochemical blood gas analysers.…”
Section: Blood Phmentioning
confidence: 63%
“…The probe (OD=0.6 mm) has been tested in-vivo on animals 40,41 and has shown satisfactory correlation with data obtained ex-vivo from electrochemical blood gas analysers.…”
Section: Phmentioning
confidence: 80%
“…41 Recent results on ferroelectric liquid crystals seem to be more promising. Both the theoretical analysis and the experiment showed that in the ON state some components of hybrid modes are wellguided and other components are cut off; in the OFF state all components are cut off.…”
Section: Optical Microsystems Utilising Liquid Crystalsmentioning
confidence: 99%